2011
DOI: 10.1097/igc.0b013e31820d3e5b
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Arising From Mature Cystic Teratoma of the Ovary

Abstract: : With our review as basis, we recommend being cautious of the following risk factors: patient age, tumor size, ultrasound characteristics, sonar tumor vessel wave form, computed tomography, and levels of SCC and CA125 tumor markers. We suggest that patients have regular ovarian ultrasound examination. Based on our literature review, stage IA patients who undergo standardized operational procedures do well without adjuvant treatment, but such patients must be confirmed accurately with complete surgical staging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 49 publications
5
36
0
Order By: Relevance
“…It was surprising that serum SCC‐Ag was not associated with MT in the present study. The reason seems to be that SCC‐Ag is high in some benign MCT, concordant with a previous report 21. Mori et al reported on the usefulness of combining SCC‐Ag with age as a predictor of MT 23…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was surprising that serum SCC‐Ag was not associated with MT in the present study. The reason seems to be that SCC‐Ag is high in some benign MCT, concordant with a previous report 21. Mori et al reported on the usefulness of combining SCC‐Ag with age as a predictor of MT 23…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, N/L ratio is as accurate as age and tumor size to predict MT 21. Given that monitoring of N/L ratio is a simple and cost‐effective diagnostic method to predict the incidence of MT, it presents a complementary, efficient method to support a preoperative diagnosis of MT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition SCC antigen may be a useful marker to detect this disease preoperatively. 8 The malignant component of MCT sometimes exists in only a part of the lesion, causing difficulty in its identification grossly. A tumor arising in MCT may appear grossly as polypoidal mass, mural nodule or mural plaques or area of hemorrhage and necrosis.…”
Section: Case Reportmentioning
confidence: 99%
“…In high grade tumors, squamous differentiation is inconspicuous. 8 Pathologic factors, grade and mode of infiltration can provide valuable information for predicting the survival of patients with squamous cell carcinoma arising from mature cystic teratoma. When malignant transformation has occurred within a teratoma, treatment is usually tailored towards the transformed histology.…”
Section: Case Reportmentioning
confidence: 99%
“…In most cases it is not diagnosed preoperatively (16,18,19). The use of tumor markers as a diagnostic tool to discriminate MCTs and SCCs arising from an MCT is difficult to help since most of them are raised in both situations (2).…”
mentioning
confidence: 99%